Constructivist aspects of the UN Security Council’s permanent members’ conduct: the case of the USA - Stojkovski, Ljupcho (Konrad Adenauer Foundation, Republic of North Macedonia Institute for Democracy “Societas Civilis”, Skopje, 2019)
The UN Security Council is an institution that is in the spotlight of world’s attention every time there is an armed conflict. This is especially the case when the Security Council is not fulfilling its responsibility to maintain international peace due to a lack of political will or the use of the veto by a permanent five (P5) member state. Therefore, the conduct of the P5 in the Security Council has a great impact on the functioning of the Council as an institution. However, even though all P5 have an equal veto power, this does not imply that all of them act identically (or in a similar manner) within and towards the Security Council. To the contrary. There are major differences among them, and (sometimes) in the behavior of a single member state throughout the years. For instance, after the end of the Cold War, the United Kingdom and France – unlike the other three permanent member states – have not used their right to veto at all. On the other hand, Russia, which just like the United Kingdom and France, has had a decrease in its power after the collapse of the Soviet Union, is the permanent member that has used the veto most frequently since the Cold War. In the case of the USA, there is a significant decrease in the use of veto after the end of the Cold War, although their military (and until recently, their economic) power has been stable and unsurpassable in the near future. There are similar differences among the P5 with regards to the idea of limitating the veto in situations of mass atrocities – an initiative known as the ‘Responsibility not to veto’. In order to understand these differences, one should examine the non-material factors, i.e. the ideas, values and identities of these states, beside the material factors and the power relations. The reason for this, following the constructivist approach in international relations (IR) theory, is that the material resources are not an independent factor, but gain importance only through the ideas that make them up. Along this line, the institutions where states are members do not only reflect their power but also their ideas, perspectives and perceptions about themselves, about the institutions that they are part of, and about how these entities, and international politics in general, (ought to) function. Therefore, it is necessary to take into consideration the non-material factors regarding the Security Council, i.e. the ‘constructivist aspects’ of the conduct – the ideas, the values, the identities, the language – of the actors that consist this body, especially the permanent five. In this paper I analyze the constructivist aspects of the conduct of one permanent member of the UN Security Council – the United States. The USA supports and sometimes works through the Security Council, but not by all means – if this body is an obstacle to its plans, it may also bypass it. This attitude of the USA towards and within the Security Council, from material perspective, is closely related to the enormous military and economic power it has globally. The non-material factors that explain this behavior include the roles of creator-reformer and custodian of the international order played by the USA, their self-perception of exceptionality, as well as their national political considerations.
Keywords: UN Security Council; Constructivism; International Relations